ROKOK SEBAGAI UPAYA PENCEGAHAN PENYAKIT JANTUNG KORONER - Hadi Saputro, Suyatno; Lukluk Atul Lababah, Ainiyatul; Agustin, Ratna (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: To determine the factors of cigarette consumption as a trigger for coronary heart disease through a Literature Review. Methods: Literature Review of the prevention of cigarette consumption in coronary heart disease patients and search for articles via the internet with pubmed databases and Scient Direct. There were 10 articles in the review. Starting from 2010-2020, 10 articles in English and full text. Results: Smoking is a factor in the occurrence of coronary heart disease due to the substances contained. Conclusion: Smoking is one of the risk factors for coronary heart disease. It takes public awareness and serious intention to take precautions so that the incidence of CHD by smoking regardless of age can decrease.